2021
DOI: 10.1177/13591045211026160
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality to treat aggressive behavior problems in children: A feasibility study

Abstract: Evidence-based cognitive behavioral therapies (CBTs) for children with aggressive behavior problems have only modest effects. Research is needed into new methods to enhance CBT effectiveness. The aims of the present study were to (1) examine whether interactive virtual reality is a feasible treatment method for children with aggressive behavior problems; (2) investigate children’s appreciation of the method; and (3) explore whether children’s aggression decreased during the ten-session treatment. Six boys (8–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…Third, the lack of significant effects on perceived behavioral control outcomes suggests that program developers may have to look at effective methods of teaching sexual and relationship competence and skills beyond role-plays and discussions. For instance, in research on general aggressive behavior in male youth, there is an upcoming use of VR methods to let participants safely practice in almost real-life aggression-invoking situations (Alsem et al, 2021).…”
Section: Suggestions For Practicementioning
confidence: 99%
“…Third, the lack of significant effects on perceived behavioral control outcomes suggests that program developers may have to look at effective methods of teaching sexual and relationship competence and skills beyond role-plays and discussions. For instance, in research on general aggressive behavior in male youth, there is an upcoming use of VR methods to let participants safely practice in almost real-life aggression-invoking situations (Alsem et al, 2021).…”
Section: Suggestions For Practicementioning
confidence: 99%
“…The aim of YourSkills is to reduce children's aggressive behavior problems by enhancing emotion regulation and social information processing skills. Children practice anger recognition, anger regulation, nonhostile intent attribution, and other social problem solving skills in social interactions (for an overview of the treatment sessions, see: Alsem et al, 2021). To enable children to practice their skills or new cognitions whilst being emotionally engaged, therapists create challenging social situations for children in virtual reality or roleplays.…”
Section: Yourskills Treatmentmentioning
confidence: 99%
“…We examined our research questions within the intervention YourSkills. In this manualized cognitive behavior therapy (CBT), children practice anger regulation and intent attribution skills during social interactions that are either simulated in virtual reality or roleplayed by a therapist (Alsem et al, 2021). In a previous study, we found that both the virtual reality and roleplay versions of YourSkills were more likely to reduce children's aggressive behavior than care-as-usual for six out of seven aggression outcomes, with some indications that virtual reality outperformed roleplay .…”
Section: Introductionmentioning
confidence: 96%
“…The disorder often includes premature sexual activity, persistent physical or verbal contacts, emotional outbursts, recklessness, antisocial behavior, and low self-esteem [23]. Interventions with the aim of evaluating this type of disorder using VR-based solutions have been reported to be effective [23][24][25].…”
Section: Conduct Disordermentioning
confidence: 99%